The Degree to which Teachers Use Functional Skills of Students with Intellectual Disabilities - Algolaylat, Ahmad; Alnjadat, Hussein; Alzboun, Ahmed (Dirasat: Educational Sciences, 2022)
Objectives: The study aims to determine the degree to which teachers use functional skills for students with intellectual disabilities according to the variables of experience, educational qualification, and gender. Methods: A total of 200 male and female teachers working in special education centers in Jordan participated in the study. To achieve the objective of the study, a list of the functional skills necessary for students with intellectual disabilities was developed. The study tool had acceptable reliability and validity indications. Results: The results indicated that the degree of teachers' use of the functional skills of students with intellectual disabilities for the tool as a whole was high with an arithmetic mean of (3.44), and was high in all areas, as well. The highest was for the decision-making skill with an arithmetic mean of (3.67), then followed by an arithmetic mean of (3.56) for the skill of professional preparation, and finally the field of daily life skills with an arithmetic mean of (3.27). The results also showed that there were no statistically significant differences due to the variables of years of experience, gender or educational qualification in all skills and in the degree of importance as a whole. Conclusions: The researcher recommends conducting more studies and research specialized in the contents of functional skills in order to identify the most important skills that people with intellectual disabilities need.